A collagen composition for repairing skin damage and a production method thereof

By crosslinking modified antibacterial cellulose with sodium alginate and collagen, a gel dressing with excellent antibacterial properties was prepared, which solved the shortcomings of traditional gel dressings in antibacterial and scar improvement, and achieved the effects of wound healing and scar reduction.

CN116196465BActive Publication Date: 2025-04-18深圳市迈捷生命科学有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211713355.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-04-18
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

Traditional gel dressings lack antibacterial properties and scar improvement capabilities in promoting wound healing, making it difficult to effectively prevent wound infection and reduce scar formation.

Method used

By preparing modified antibacterial cellulose and using zinc chloride as a crosslinking agent, it is crosslinked with sodium alginate and collagen to form a collagen composition gel dressing with excellent antibacterial properties.

Benefits of technology

This gel dressing not only has good antibacterial properties, can effectively prevent wound infection, but also promote wound healing and reduce scar formation, improving wound repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004027244090000081
    Figure BDA0004027244090000081
  • Figure BDA0004027244090000091
    Figure BDA0004027244090000091
  • Figure BDA0004027244090000092
    Figure BDA0004027244090000092
Patent Text Reader

Abstract

The invention relates to the technical field of skin damage repair, and discloses a collagen composition for skin damage repair and a production method thereof. The collagen composition comprises sodium alginate, polyvinyl alcohol, glycerol, collagen, zinc chloride, and modified antibacterial cellulose. L-arginine is introduced into the cellulose structure to give the cellulose good antibacterial properties. Zinc chloride is used as a cross-linking agent to cross-link the zinc chloride with sodium alginate to obtain a composition gel dressing with good antibacterial properties. The added collagen can penetrate the stratum corneum and combine with skin epithelial cells, participate in skin cell metabolism, enhance the activity of collagen in the skin, assist cells in producing collagen, promote the rapid growth of skin cells, and help leave no scars on the wound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of skin damage repair, and in particular to a collagen composition for skin damage repair and a production method thereof. Background Art

[0002] In the human body, the skin is the largest organ, and its main function is to prevent the volatilization of effective ingredients such as water and electrolytes in the body, and at the same time prevent harmful substances from directly entering the body and causing adverse effects on human health. In daily life, it is inevitable that bumps, burns, medical operations and other factors will cause skin damage, which will not only cause the skin to lose its protective function, but may also cause permanent scars or pigmentation due to improper wound treatment. Gel dressings are a new type of wound auxiliary material that has developed rapidly in recent years. It is a gel-like substance with a three-dimensional network structure and is insoluble in water. Covering it on the wound can avoid secondary damage to the wound and is beneficial to wound healing. However, traditional gel dressings often need to be prepared using chemically synthesized polymers, and it is difficult to ensure that they are not biologically toxic. Therefore, in recent years, research on gel dressings has mainly focused on the field of natural polymer materials.

[0003] The Chinese invention patent with application number CN202110287281.3 discloses a method for preparing a sodium alginate nanosilver antibacterial hydrogel dressing. Sodium alginate is used as a carrier to immobilize nanosilver in sodium alginate, and nanosilver and silver ions are gradually released through a sustained-controlled release effect, which can not only maintain a certain effective concentration, but also reduce the harm caused by the aggregation and migration of nanosilver, so that the prepared hydrogel dressing has good antibacterial activity and biocompatibility, which is beneficial to promote wound healing. However, the hydrogel dressing prepared by this method only promotes wound healing from an antibacterial perspective, and cannot guarantee that no scars will be left on the wound after healing. Collagen has a greater affinity with protein molecules on the skin surface, weaker antigenicity and good biocompatibility. Therefore, collagen can be added in the preparation process of the gel dressing to prepare a gel dressing with excellent wound repair performance. Summary of the invention

[0004] The purpose of the present invention is to provide a collagen composition for skin damage repair and a production method thereof. The modified antibacterial cellulose is prepared and zinc chloride is used as a cross-linking agent to cross-link it with active substances such as sodium alginate and collagen to prepare a collagen composition gel dressing with excellent antibacterial properties, which can promote wound healing and improve scars on wounds.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A collagen composition for repairing skin damage, comprising the following raw materials in parts by weight: 50-60 parts of sodium alginate, 30-40 parts of polyvinyl alcohol, 10-20 parts of glycerol, 5-10 parts of collagen, 4-8 parts of zinc chloride, and 2-6 parts of modified antibacterial cellulose;

[0007] The modified antibacterial cellulose is prepared by esterifying cellulose and then connecting an amino acid antibacterial agent through an aminolysis reaction.

[0008] Furthermore, the production method of the modified antibacterial cellulose specifically comprises the following steps:

[0009] S1: Disperse hydroxyethyl cellulose in tetrahydrofuran, stir well, add dimethyl succinate, use sodium hydroxide solution to adjust the pH of the system to 8-9, stir at 60-70°C for 2-6h, wait for the material to cool, use dilute hydrochloric acid to adjust the pH of the system to neutral, filter, wash, and vacuum dry to prepare esterified cellulose;

[0010] S2: Mix the esterified cellulose with N,N-dimethylformamide, add L-arginine, use hydrochloric acid solution to adjust the pH value of the system, stir for 4-12 hours at a temperature of 50-60°C, wait for the reaction to end, settle, wash the material with a 70% by volume ethanol solution, and vacuum dry to prepare modified antibacterial cellulose.

[0011] Through the above technical scheme, in an alkaline environment, the hydroxyl group in the hydroxyethyl cellulose structure can undergo an ester exchange reaction with the ester group in the dimethyl succinate structure, and by controlling the dosage of hydroxyethyl cellulose and dimethyl succinate, an esterified cellulose containing an ester group in the structure can be obtained, and the ester group in the structure can produce an aminolysis reaction with the amino group in the L-arginine structure, thereby introducing the carboxyl group and guanidine group in the L-arginine structure into the cellulose structure to obtain modified antibacterial cellulose.

[0012] Furthermore, in step S1, the mass ratio of hydroxyethyl cellulose to dimethyl succinate is 1:0.1-0.25.

[0013] Furthermore, in step S1, the volume fraction of the sodium hydroxide solution is 2-4%.

[0014] Furthermore, in step S1, the concentration of the dilute hydrochloric acid is 0.4-0.5 mol / L.

[0015] Furthermore, in step S2, the concentration of the hydrochloric acid solution is 1-1.5 mol / L.

[0016] Furthermore, in step S2, the pH value is adjusted to 5-6.

[0017] A method for producing a collagen composition for repairing skin damage comprises the following steps:

[0018] SS1: Mix sodium alginate, collagen, polyvinyl alcohol and glycerol with deionized water, stir well and let stand to degas to obtain a gel solution;

[0019] SS2: Pour the modified antibacterial cellulose and anhydrous zinc chloride into deionized water, add glacial acetic acid to promote dissolution, stir evenly, and stand to degas to obtain a crosslinker solution;

[0020] SS3: Pour the gel solution into a mold, refrigerate it at 0-5°C for 1-3 hours, then take it out, add the crosslinker solution into the mold, stir it at room temperature for 12-24 hours, pour out the material, and wash it with deionized water to obtain a gel collagen composition.

[0021] Through the above technical scheme, sodium alginate is a natural polymer material with good biodegradability and biocompatibility, which is widely used in hemostatic dressings. Polyvinyl alcohol is a non-toxic, non-irritating hydrophilic polymer with a large number of hydroxyl functional groups in its structure, which can absorb a large amount of water and form strong hydrogen bonds. It also has good film-forming properties and is conducive to the formation of gel. Both sodium alginate and modified antibacterial cellulose contain carboxyl groups in their structures, which will ionize in aqueous solution to produce carboxyl anions, which can react with multivalent metal ions to cross-link and produce sodium alginate-Zn 2+ -The modified antibacterial cellulose three-dimensional cross-linked network, during the cross-linking reaction, collagen is wrapped in the gel to form a gel-like collagen composition that wraps collagen.

[0022] Beneficial effects of the present invention:

[0023] 1) The present invention introduces L-arginine into the cellulose structure, thereby introducing the guanidine group in the arginine structure into the cellulose structure, wherein the guanidine group can show extremely strong positive charge, and its protonated structure can be adsorbed on the surface of the negatively charged bacterial cell wall to form a polymer film, thereby preventing the entry of nutrients and the discharge of metabolites, causing metabolic disorders of bacterial microorganisms, and ultimately leading to the death of bacteria, thereby giving cellulose good antibacterial properties. The composition gel dressing prepared by cross-linking the cellulose with sodium alginate has good antibacterial properties, can effectively prevent bacterial infection at the wound, and thus promote wound healing.

[0024] 2) After L-arginine is introduced into the cellulose structure, carboxyl groups are generated in the cellulose structure. The principle of cross-linking reaction between carboxyl anions and high-valent metal ions can be utilized, and zinc chloride is used as a cross-linking agent to make the prepared composite gel dressing contain a large amount of zinc ions. After the zinc ions come into contact with the bacteria, they will combine with the active proteases in the bacteria to make them lose their activity, thereby killing the bacteria. The zinc ions can produce a synergistic antibacterial effect with the guanidine groups in the cellulose structure, further enhancing the antibacterial effect of the gel dressing.

[0025] 3) In the process of preparing the gel dressing, collagen is added, which can penetrate the stratum corneum and combine with the skin epithelial cells, participate in the metabolism of skin cells, enhance the activity of collagen in the skin, assist cells to produce collagen, promote the rapid growth of skin cells, and help the wound to leave no scars. 2+ -The modified antibacterial cellulose three-dimensional cross-linked network can achieve a slow release effect, which is beneficial to wound healing and avoids the extra pain caused to patients by frequent dressing changes.

[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A collagen composition for repairing skin damage, comprising the following raw materials in parts by weight: 50 parts of sodium alginate, 30 parts of polyvinyl alcohol, 10 parts of glycerol, 5 parts of collagen, 4 parts of zinc chloride, and 2 parts of modified antibacterial cellulose;

[0030] The production method of the collagen composition comprises the following steps:

[0031] SS1: Mix sodium alginate, collagen, polyvinyl alcohol and glycerol with deionized water, stir well and let stand to degas to obtain a gel solution;

[0032] SS2: Pour the modified antibacterial cellulose and anhydrous zinc chloride into deionized water, add glacial acetic acid to promote dissolution, stir evenly, and stand to degas to obtain a crosslinker solution;

[0033] SS3: Pour the gel solution into a mold, refrigerate it at 0°C for 1 hour, then take it out, add the crosslinker solution into the mold, stir it at room temperature for 12 hours, pour out the material, and wash it with deionized water to obtain a gel collagen composition.

[0034] The production method of modified antibacterial cellulose comprises the following steps:

[0035] S1: Disperse 10 g of hydroxyethyl cellulose in tetrahydrofuran, stir well, add 2 g of dimethyl succinate, use a 3% volume fraction of sodium hydroxide solution to adjust the system pH to 8.5, stir at 70°C for 4 hours, wait for the material to cool, use a 0.5 mol / L dilute hydrochloric acid solution to adjust the system pH to neutral, filter, wash, and vacuum dry to prepare esterified cellulose;

[0036] S2: Mix 5 g of esterified cellulose with N,N-dimethylformamide, add 1.5 g of L-arginine, adjust the pH of the system to 5 with a hydrochloric acid solution with a concentration of 1 mol / L, stir at a temperature of 50°C for 8 hours, wait for the reaction to be completed, settle, wash the material with a 70% by volume ethanol solution, and vacuum dry to prepare modified antibacterial cellulose.

[0037] Example 2

[0038] A collagen composition for repairing skin damage, comprising the following raw materials in parts by weight: 55 parts of sodium alginate, 35 parts of polyvinyl alcohol, 15 parts of glycerol, 8 parts of collagen, 6 parts of zinc chloride, and 4 parts of modified antibacterial cellulose;

[0039] The production method of the collagen composition comprises the following steps:

[0040] SS1: Mix sodium alginate, collagen, polyvinyl alcohol and glycerol with deionized water, stir well and let stand to degas to obtain a gel solution;

[0041] SS2: Pour the modified antibacterial cellulose and anhydrous zinc chloride into deionized water, add glacial acetic acid to promote dissolution, stir evenly, and stand to degas to obtain a crosslinker solution;

[0042] SS3: Pour the gel solution into a mold, refrigerate it at 5°C for 2 hours, then take it out, add the crosslinker solution into the mold, stir it at room temperature for 16 hours, pour out the material, and wash it with deionized water to obtain a gel collagen composition.

[0043] The production method of the modified antibacterial cellulose is the same as that in Example 1.

[0044] Example 3

[0045] A collagen composition for repairing skin damage, comprising the following raw materials in parts by weight: 60 parts of sodium alginate, 40 parts of polyvinyl alcohol, 20 parts of glycerol, 10 parts of collagen, 8 parts of zinc chloride, and 6 parts of modified antibacterial cellulose;

[0046] The production method of the collagen composition comprises the following steps:

[0047] SS1: Mix sodium alginate, collagen, polyvinyl alcohol and glycerol with deionized water, stir well and let stand to degas to obtain a gel solution;

[0048] SS2: Pour the modified antibacterial cellulose and anhydrous zinc chloride into deionized water, add glacial acetic acid to promote dissolution, stir evenly, and stand to degas to obtain a crosslinker solution;

[0049] SS3: Pour the gel solution into a mold, refrigerate it at 5°C for 3 hours, then take it out, add the crosslinker solution into the mold, stir it at room temperature for 24 hours, pour out the material, and wash it with deionized water to obtain a gel collagen composition.

[0050] The production method of the modified antibacterial cellulose is the same as that in Example 1.

[0051] Comparative Example 1

[0052] A collagen composition for repairing skin damage, comprising the following raw materials in parts by weight: 55 parts of sodium alginate, 35 parts of polyvinyl alcohol, 15 parts of glycerol, 8 parts of collagen, 6 parts of zinc chloride, and 4 parts of carboxymethyl cellulose;

[0053] The production method of the collagen composition comprises the following steps:

[0054] SS1: Mix sodium alginate, collagen, polyvinyl alcohol and glycerol with deionized water, stir well and let stand to degas to obtain a gel solution;

[0055] SS2: Pour carboxymethyl cellulose and anhydrous zinc chloride into deionized water, add glacial acetic acid to promote dissolution, stir evenly, and let stand to degas to obtain a crosslinker solution;

[0056] SS3: Pour the gel solution into a mold, refrigerate it at 5°C for 2 hours, then take it out, add the crosslinker solution into the mold, stir it at room temperature for 16 hours, pour out the material, and wash it with deionized water to obtain a gel collagen composition.

[0057] Performance Testing

[0058] A. The collagen compositions prepared in Examples 1 to 3 of the present invention and Comparative Example 1 were cut into round gel samples with a diameter of 10 mm and a thickness of 2 mm. 0.3 mL of Staphylococcus aureus was placed in beef broth and cultured at 37° C. for 24 h. The samples were diluted 10-6 times, make the test bacterial suspension, pipette 0.3mL of bacterial suspension onto the surface of the gel sample, culture for 12h, wash the gel sample with sterile water, absorb 0.3mL of washing solution, continue to culture on the culture dish for 24h, record the number of colonies on the culture dish, and do a blank control test, using the formula

[0059]

[0060] Calculate the antibacterial rate of the sample, where S0 is the colony count of the blank control experimental group, S1 is the colony count of each sample, and P is the antibacterial rate. The test results are as follows:

[0061]

[0062] It can be seen from the above table that the gel-like collagen compositions prepared in Examples 1 to 3 of the present invention have excellent antibacterial properties, with an average antibacterial rate of more than 99%, while the gel-like collagen composition prepared in Comparative Example 1 has slightly poor antibacterial properties. It is speculated that after cross-linking with zinc chloride, the gel-like collagen composition contains a large amount of zinc ions. After the zinc ions come into contact with bacteria, they will combine with the active proteases in the bacteria, causing them to lose their activity, thereby causing the bacteria to die. However, the component does not contain guanidine synergistic antibacterial groups, resulting in slightly poor antibacterial properties.

[0063] B. Fifty rats weighing about 200 g were randomly selected and divided into five groups with an average of 10 rats in each group, namely, Example 1 to Example 3, Comparative Example 1 and a blank control experimental group. The hair on the back of the mice was removed, and a 1 cm × 1 cm injury wound was scanned at the same position on the back of the mice with a laser, and the gel-like collagen composition prepared in Example 1 to Example 3 of the present invention and Comparative Example 1 was covered respectively, once a day for 30 min each time. The wounds of the mice in the blank group were exposed to the air, and the healing of the wounds on the back of the mice was observed. The test results are as follows:

[0064]

[0065]

[0066] As can be seen from the above table, the gel-like collagen compositions prepared in Examples 1 to 3 of the present invention and Comparative Example 1 can heal the wounds of mice in about 7 days, and no obvious scars will be produced after the wounds are completely healed. However, the gel-like collagen composition prepared in Comparative Example 1 has a slightly weaker antibacterial property, with slight redness and swelling at 3 days, while the wounds of the mice in the blank control group were obviously infected at 3 days, and obvious scars were left after the wounds healed. It is speculated that the addition of collagen can penetrate the stratum corneum and combine with skin epithelial cells, participate in skin cell metabolism, enhance the activity of collagen in the skin, assist cells in producing collagen, promote rapid growth of skin cells, and is beneficial to leaving no scars on the wounds.

[0067] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A collagen composition for repairing skin damage, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of sodium alginate, 30-40 parts of polyvinyl alcohol, 10-20 parts of glycerol, 5-10 parts of collagen, 4-8 parts of zinc chloride and 2-6 parts of modified antibacterial cellulose; The modified antibacterial cellulose is prepared by esterifying cellulose and then connecting an amino acid antibacterial agent through an aminolysis reaction; The production method of the modified antibacterial cellulose specifically comprises the following steps: S1: Disperse hydroxyethyl cellulose in tetrahydrofuran, stir well, add dimethyl succinate, use sodium hydroxide solution to adjust the pH of the system to 8-9, stir at 60-70°C for 2-6h, wait for the material to cool, use dilute hydrochloric acid to adjust the pH of the system to neutral, filter, wash, and vacuum dry to prepare esterified cellulose; S2: Mix the esterified cellulose with N,N-dimethylformamide, add L-arginine, use hydrochloric acid solution to adjust the pH value of the system, stir for 4-12 hours at a temperature of 50-60°C, wait for the reaction to end, settle, wash the material with a 70% by volume ethanol solution, and vacuum dry to prepare modified antibacterial cellulose.

2. A collagen composition for skin damage repair according to claim 1, characterized in that: In step S1, the mass ratio of hydroxyethyl cellulose to dimethyl succinate is 1:0.1-0.

25.

3. A collagen composition for skin damage repair according to claim 1, characterized in that: In step S1, the volume fraction of the sodium hydroxide solution is 2-4%.

4. The collagen composition for skin damage repair according to claim 1, characterized in that: In step S1, the concentration of the dilute hydrochloric acid is 0.4-0.5 mol / L.

5. The collagen composition for skin damage repair according to claim 1, characterized in that: In step S2, the concentration of the hydrochloric acid solution is 1-1.5 mol / L.

6. The collagen composition for skin damage repair according to claim 1, characterized in that: In step S2, the pH value is adjusted to 5-6.

7. A method for producing a collagen composition for skin damage repair according to claim 1, characterized in that: The production method comprises the following steps: SS1: Mix sodium alginate, collagen, polyvinyl alcohol and glycerol with deionized water, stir well and let stand to degas to obtain a gel solution; SS2: Pour the modified antibacterial cellulose and anhydrous zinc chloride into deionized water, add glacial acetic acid to promote dissolution, stir evenly, and stand to degas to obtain a crosslinker solution; SS3: Pour the gel solution into a mold, refrigerate it at 0-5°C for 1-3 hours, then take it out, add the crosslinker solution into the mold, stir it at room temperature for 12-24 hours, pour out the material, and wash it with deionized water to obtain a gel collagen composition.

Citation Information

Patent Citations

  • A method for preparing a sodium alginate nano-silver antibacterial hydrogel dressing

    CN113018505B

  • Marine biomaterial composite hydrogel dressing and preparation method thereof

    CN108014366A

  • Partial ester of cellulose with nitrogenous carboxylic acid and process for producing the same

    US20030027733A1